Comparative spatial genetics and epigenetics of plant populations: heuristic value and a proof of concept. Issue 8 (14th March 2016) - Herrera, Carlos M.; Medrano, Mónica; Bazaga, Pilar
Abstract: Despite the recent upsurge of interest on natural epigenetic variation of nonmodel organisms, factors conditioning the spatial structure of epigenetic diversity in wild plant populations remain virtually unexplored. We propose that information on processes shaping natural epigenetic variation can be gained using the spatial structure of genetic diversity as null model. Departures of epigenetic isolation‐by‐distance (IBD) patterns from genetic IBD patterns for the same sample, particularly differences in slope of similarity‐distance regressions, will reflect the action of factors that operate specifically on epigenetic variation, including imperfect transgenerational inheritance and responsiveness to environmental factors of epigenetic marks. As a proof of concept, we provide a comparative analysis of spatial genetic and epigenetic structure of 200 mapped individuals of the perennial herb Helleborus foetidus . Plants were fingerprinted using nuclear microsatellites, amplified fragment length polymorphisms (AFLP) and methylation‐sensitive AFLP markers. Expectations from individual‐level IBD patterns were tested by means of kinship‐distance regressions. Both genetic and epigenetic similarity between H. foetidus individuals conformed to theoretical expectations under individual‐level IBD models. Irrespective of marker type, there were significant negative linear relationships between the kinship coefficient for plant pairs and their spatial separation. Regression slopes were significantly steeper for epigenetic markers. Epigenetic similarity between individuals was much greater than genetic similarity at shortest distances, such epigenetic 'kinship excess' tending to decrease as plant separation increased. Results suggest that moderate‐to‐high heritability and responsiveness to local environments are major drivers of epigenetic spatial structure in H. foetidus, and illustrate the heuristic value of comparing genetic and epigenetic spatial structure for formulating and testing hypotheses on forces shaping epigenetic diversity in wild plant populations.